2005
DOI: 10.2214/ajr.185.2.01850533
|View full text |Cite
|
Sign up to set email alerts
|

Chest Pain Evaluation in the Emergency Department: Can MDCT Provide a Comprehensive Evaluation?

Abstract: ECG-gated MDCT appears to be logistically feasible and shows promise as a comprehensive method for evaluating cardiac and noncardiac chest pain in stable emergency department patients. Further hardware and software improvements will be necessary for adoption of this paradigm in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
99
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(107 citation statements)
references
References 22 publications
(22 reference statements)
4
99
0
2
Order By: Relevance
“…In a previous study from the same group [35], it was already demonstrated that MSCT appeared to be logistically feasible and showed promise as a comprehensive method for evaluating cardiac and noncardiac chest pain in stable emergency department patients [36]. Haidary et al [37] showed that the triple rule-out 64-slice biphasic injection breath-hold CT angiography protocol provided significantly higher attenuation of aortic and pulmonary vasculature compared with our current 10-and 16-slice protocols.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…In a previous study from the same group [35], it was already demonstrated that MSCT appeared to be logistically feasible and showed promise as a comprehensive method for evaluating cardiac and noncardiac chest pain in stable emergency department patients [36]. Haidary et al [37] showed that the triple rule-out 64-slice biphasic injection breath-hold CT angiography protocol provided significantly higher attenuation of aortic and pulmonary vasculature compared with our current 10-and 16-slice protocols.…”
mentioning
confidence: 62%
“…The use of triple rule-out protocol has been reported in several studies [36][37][38][39][40]. In a previous study from the same group [35], it was already demonstrated that MSCT appeared to be logistically feasible and showed promise as a comprehensive method for evaluating cardiac and noncardiac chest pain in stable emergency department patients [36].…”
mentioning
confidence: 97%
“…White et al studied 78 ED patients with acute chest pain, excluding those who were clinically unstable, had definite myocardial infarction, or deemed unlikely to have a significant cause of chest pain [43]. Patients consented to the 16-slice MDCT as an additional study.…”
Section: Emergency Medicine Literaturementioning
confidence: 99%
“…White et al diagnosed 3 patients with non-coronary diseases: one patient each with pulmonary embolism, pericardial effusion, and pneumonia [43]. One study of 151 low-risk patients with chest pain found that 11.9% of patients had significant noncardiac findings, including hiatal hernias, esophageal inflammation, pulmonary infiltrate, and pericardial effusion.…”
Section: Emergency Medicine Literaturementioning
confidence: 99%
“…However, when CTA reveals coronary stenoses of uncertain significance, further testing would be indicated (13). Although some institutions do not perform coronary CTA in patients suspected of having acute coronary syndromes (12), others use CTA in the emergency department to rule out pulmonary embolism, acute coronary syndrome, and aortic dissection in a single study (the so-called "triple rule-out") (14). Early triage of patients with acute chest pain remains difficult and is often not effective.…”
Section: Indications For Cardiac Ctmentioning
confidence: 99%